P144 Optimising chlamydia screening – a city and countywide approach in nottinghamshire. (8th June 2017) - Handley, Sally; Shaw, Deborah; Neal, Carl; Ford, Carol; Romilly, Nick; Gribbin, Jonathan; Saunders, John; Taylor, Ruth; Carlin, Elizabeth
Abstract : Introduction: The Public Health Outcomes Framework detection rate indicator (DRI) sets a target of ≥2, 300 chlamydia diagnoses per 100, 000 15 to 24 year-olds. The 2014 DRI in Nottingham City and Nottinghamshire County was 2, 807 and 1, 900, respectively. We used the National Chlamydia Screening Programme's Chlamydia Care Pathway (CCP) approach to review 2014 data and identify opportunities to improve the quality of screening and increase the DRI. Methods: Routine surveillance data from GUMCAD and CTAD was used to populate the CCP for the region. Findings were discussed at the local strategic sexual health group and actions agreed. Results: Issues identified were around unknown test offer-rate, low coverage in some districts and low retesting rates following treatment. In response: existing GUMCAD codes were used to infer the offer of a test; health promotion activities focused on raising awareness of testing among key populations, primary care and providers of other young person services; re-testing pathways were audited and a text reminder system for re-screening at 3months was implemented in one of the units. Discussion: The CCP provided a strategic focus to increase understanding of screening at all stages of the pathway. It confirmed the need for an integrated screening approach across sexual health providers, primary care and broader health services who engage with young people. There was potential to achieve 'quick wins' by using the CCP to focus on each specific stage of the programme. 2017 data will be reviewed using the CCP to evaluate the impact of the plans which have been implemented.